Thiobacillus ferrooxidans response to copper and other heavy metals: growth, protein synthesis and protein phosphorylation - Novo, MTM; da Silva, A. C.; Moreto, R.; Cabral, PCP; Costacurta, A.; Garcia, O.; Ottoboni, LMM (Kluwer Academic Publ, 2000)
Respirometric experiments demonstrated that the oxygen uptake by Thiobacillus ferrooxidans strain LR was not inhibited in the presence of 200 mM copper. Copper-treated and untreated cells from this T. ferrooxidans strain were used in growth experiments in the presence of cadmium, copper, nickel and zinc. Growth in the presence of copper was improved by the copper-treated cells. However, no growth was observed for these cells, within 190 h of culture, when cadmium, nickel and zinc were added to the media. Changes in the total protein synthesis pattern were detected by two-dimensional polyacrylamide gel electrophoresis for T. ferrooxidans LR cells grown in the presence of different heavy metals. Specific proteins were induced by copper (16, 28 and 42 kDa) and cadmium (66 kDa), whereas proteins that had their synthesis repressed were observed for all the heavy metals tested. Protein induction was also observed in the cytosolic and membrane fractions from T. ferrooxidans LR cells grown in the presence of copper. The level of protein phosphorylation was increased in the presence of this metal.
Keywords: growth curves; heavy metals; protein phosphorylation; protein synthesis; T. ferrooxidans